Multicultural learning community: Students’ experiences of studies in education program at the School of Education, University of Iceland - Ragnarsdóttir, Hanna; Blöndal, Hildur (Icelandic Journal of Education, 2015)
In this research we take a specific look at the International Studies in Education program at the University of Iceland’s School of Education where we seek to explore if and how the program and its underlying ideology of critical pedagogy has influenced the lives of seven participating women who all have an immigrant background. Through their stories we learn more about if and how being a part of this particular program has affected them in a personal way. Drawing on the knowledge gained through personal narratives and focus group interviews we seek to answer these key research questions: How can education be a key element in the empowerment of immigrant students and provide them with opportunities to reach their full potential? Where do students seek support and guidance? How can a higher education program based on critical pedagogy facilitate the empowerment of students with an immigrant background? The study has two components, a personal narrative, where participants write about their educational experience in the International Studies in Education program and focus group interviews with 3–4 participants. With globalization we have seen increased global mobility and as a result societies that are more culturally diverse than just a few decades ago. These societal changes are an inspiration for the educational researcher. They bring with them new opportunities and new ideas for research. “Globalization is a multifaceted process with economic, social, political and cultural implications for higher education” (UNESCO, 2004). Societal changes in Iceland with growing numbers of immigrants in the past 15 years (Hagstofa Íslands, 2012) have led to increasing numbers of immigrant students in Icelandic universities. Some of these students have struggled with pursuing their studies in Icelandic and some previous research findings have indicated their marginalization in these programs (Hanna Ragnarsdóttir & Hildur Blöndal, 2007). As a response to this new reality, the decision was made to develop an international ...